Mask-Wearing Increased After a Government Recommendation: A Natural Experiment in the U.S. During the COVID-19 Pandemic - Goldberg, Matthew H.; Gustafson, Abel; Maibach, Edward W.; Ballew, Matthew T.; Bergquist, Parrish; Kotcher, John E.; Marlon, Jennifer R.; Rosenthal, Seth A.; Leiserowitz, Anthony (Frontiers in Communication, 2020)
On April 3 2020, the U.S. Centers for Disease Control and Prevention (CDC) recommended that all Americans wear face masks to prevent the spread of COVID-19. The announcement came during the fielding of a large, nationally-representative survey (N = 3,933) of Americans’ COVID-19-related knowledge, attitudes, and behaviors, providing an opportunity to measure the impact of the CDC’s recommendation on public reported mask wearing and buying behavior. The study found significant increases in reported mask wearing (+12 percentage points) and mask buying (+7 points). These findings indicate the speed with which government recommendations can affect the adoption of protective behaviors by the public. The results demonstrate the importance of national leadership and communication during a public health crisis.